2000
DOI: 10.1161/01.cir.102.6.630
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Response to Treatment in Coronary Heart Disease

Abstract: Decreased LVEF, type D personality, and younger age increase the risk of cardiac events; convergence of these factors predicts nonresponse to treatment. Emotionally stressed and younger patients with CHD represent high-risk groups deserving of special study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
149
1
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(162 citation statements)
references
References 30 publications
6
149
1
6
Order By: Relevance
“…Conventionally, a median split on both scales is used to identify Type D (e.g., Denollet, 1998;Denollet et al, 2000;Pedersen and Middel, 2001), and good internal reliability has been reported (Denollet, 1998). In the present sample, Cronbach's α for the NA and SI scales was .87 and .75, respectively, indicating acceptable internal consistency.…”
Section: Materials and Apparatusmentioning
confidence: 51%
See 2 more Smart Citations
“…Conventionally, a median split on both scales is used to identify Type D (e.g., Denollet, 1998;Denollet et al, 2000;Pedersen and Middel, 2001), and good internal reliability has been reported (Denollet, 1998). In the present sample, Cronbach's α for the NA and SI scales was .87 and .75, respectively, indicating acceptable internal consistency.…”
Section: Materials and Apparatusmentioning
confidence: 51%
“…Studies have linked Type D personality with cardiac and all-cause mortality (e.g., Denollet et al, 1996;Denollet et al, 2000) and increased cardiac morbidity (Denollet and Brutsaert, 1998). Furthermore, the Type D personality has been shown to be a predictor of patient adjustment to disease interventions (e.g., .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found a non-significant interaction effect for Type D personality by time, indicating that personality did not moderate the effects of cardiac rehabilitation on health status but exerted a stable effect on health status over time. In a mixed group of cardiac patients attending cardiac rehabilitation, patients with a Type D personality were also shown to report poorer health status, but this study only evaluated health status at one time point [19]. In the current study, patients with a cardiac history prior to the referral event reported impaired health status compared to patients without a cardiac history.…”
Section: Discussionmentioning
confidence: 71%
“…Type D is defined by the two normal and stable personality traits Negative Affectivity [17] and Social Inhibition [18]. Patients with this personality disposition often feel sad, have a gloomy view of life, and at the same time do not express these emotions in social interactions because of fear of disapproval or rejection by others [19].…”
mentioning
confidence: 99%